[PP.12.13] DIFFERENT EFFECTS OF ACUTE HIGH SALT INTAKE ON ANTIOXIDATIVE GENES EXPRESSION IN CEREBRAL BLOOD VESSELS IN YOUNG AND MATURE SPRAGUE-DAWLEY RATS. (September 2016) - Cosic, A.; Stupin, A.; Drenjancevic, I.
Abstract : Objective: The aim of this study was to assess the level of antioxidative genes expression in Sprague-Dawley rats at different ages and question whether high salt (HS) intake leads to the same changes regardless of the animal age. Design and method: 4- and 11-weeks old healthy male rats (N = 3–6) were divided to low salt (LS) group fed 0.4% NaCl chow and HS group fed 4% NaCl chow for 1 week. After diet protocol rats were anesthetized with ketamin-chloride (75 mg/kg) and midazolam (2.5 mg/kg) and sacrificed. All surface cerebral blood vessels were isolated and collected for mRNA gene expression analysis: SOD isoforms (Cu/ZnSOD, MnSOD, ecSOD) and glutathione peroxidase 4 (GPx4)) using real-time quantitative PCR (rtPCR; BioRad CFX96). Results are presented as mean ± SEM (p < 0.05 was considered significant). All experimental procedures conformed to the European Guidelines for the Care and Use of Laboratory Animals (directive 86/609) and were approved by the local Ethical Committee. Results: mRNA expression of SOD isoforms (MnSOD (4wLS 0.188 ± 0.012 vs. 11wLS 0.952 ± 0.078, p < 0.001) and ecSOD (4wLS 0.240 ± 0.009 vs. 11wLS 0.609 ± 0.083, p = 0.002)) was significantly higher, while expression of GPx4 (4wLS 1.299 ± 0.20 vs. 11wLS 0.819 ± 0.07, p = 0.024) was significantly decreased in older animals compared to young animals, both on a LS. mRNA expression of Cu/ZnSOD (4wLS 1.012 ± 0.02 vs. 4wHS 0.289 ± 0.17, p = 0.005) in young rats and expression of GPx4 (4wLS 1.299 ± 0.02 vs. 4wHS 0.457 ± 0.16, p = 0.031; 11wLS 0.819 ± 0.07 vs. 11wHS 0.644 ± 0.02, p = 0.041) in both age groups was significantly lower in HS groups. Expression of each SOD isoforms was increased in 11wHS rats compared to 4wHS rats (Cu/ZnSOD (4wHS 0.289 ± 0.017 vs. 11wHS 0.979 ± 0.05, p < 0.001), MnSOD (4wHS 0.022 ± 0.019 vs. 11wHS 0.792 ± 0.06, p < 0.001) and ecSOD (4wHS 0.080 ± 0.05 vs. 11wHS 0.510 ± 0.04, p < 0.001). Also the expression of MnSOD and ecSOD was significantly higher in 11wHS group compared to 4wLS group. Conclusions: The antioxidative genes expression increased with age. HS diet does not affect SOD isoform expression in older rats, but significantly decreases Cu/ZnSOD and GPx4 in young rats. Thus, harmful effects of HS intake may be more detrimental to vascular function in the younger age, due to presumably higher level of oxidative stress.